Knowledge and beliefs about national development and developmental hierarchies: The viewpoints of ordinary people in thirteen countries - Thornton, Arland (2012)
Scholars and policy makers have for centuries constructed and used developmental hierarchies to characterize different countries. The hypotheses motivating this paper are that such social constructions have been circulated internationally, are constructed similarly in various countries, and follow the social constructions of elite international organizations, such as the United Nations. This paper uses data from 15 surveys in 13 diverse countries to study how developmental hierarchies are understood in everyday life. Our research shows that most people have constructions of developmental hierarchies that are similar across countries and are similar to the developmental hierarchies constructed by the United Nations. These findings suggest that developmental hierarchies are widely understood around the world and are widely available to ordinary people as they make decisions about many aspects of life.